Volatile Organic Compounds From Breath Differ Between Patients With Major Depression and Healthy Controls - Lueno, Marian; Dobrowolny, Henrik; Gescher, Dorothee; Gbaoui, Laila; Meyer-Lotz, Gabriele; Hoeschen, Christoph; Frodl, Thomas (Frontiers in Psychiatry, 2022)
Major depressive disorder (MDD) is a widespread common disorder. Up to now, there are no easy and frequent to use non-invasive biomarkers that could guide diagnosis and treatment of MDD. The aim of this study was to investigate whether there are different mass concentrations of volatile organic compounds (VOCs) in exhaled breath between patients with MDD and healthy controls. For this purpose, patients with MDD according to DSM-V and healthy subjects were investigated. VOCs contained in the breath were collected immediately after awakening, after 30 min, and after 60 min in a respective breath sample and measured using PRT-MS (proton-transfer-reaction mass spectrometry). Concentrations of masses m/z 88, 89 and 90 were significantly decreased in patients with MDD compared to healthy controls. Moreover changes during time in mass concentrations of m/z 93 and 69 significantly differed between groups. Differentiation between groups was possible with an AUCs of 0.80 – 0.94 in ROC analyses. In this first study, VOCs differed between patients and controls and therefore, might be a promising tool for future studies. Altered masses are conceivable with energy metabolism in a variety of biochemical processes and involvement of the brain-gut-lung-microbiome axis.